Edupreneurs Parent Class TK Pembina Subah: Pemberdayaan Orangtua dalam Ekosistem Sekolah - Asmara, Franita Dian (CV. Supernova Office Stationary and Printing, 2023)
Edupreneurship is a combination of the words education (education) and entrepreneurship (entrepreneurship). Edupreneurship wants to place entrepreneurial concepts and attitudes in the world of education. In learning activities, Pembina Subah State Kindergarten has implemented the Pancasila Student Profile program, the dimension being carried out is the dimension of global diversity. This activity has the aim of introducing students to local cultivation products, namely salted eggs. So that parents feel more connected, involved, and focused on their child's development.